Healthcare Marketing: Global Molecular Diagnostics for Infectious Diseases - Iqbal, Muhammad Naeem; Hussain, Firasat; Ashraf, Asfa (International Journal of Molecular Microbiology, 2021)
The molecular diagnostics of the infectious disease sector of the clinical diagnostics industry is a market that just keeps on growing. Infectious disease testing directly benefits from the explosion in biotechnology, especially genomics. Exciting technical developments hold the promise of a dynamic, growing, and evolving world market that holds the promise of diagnostics taking the lead in infectious disease eradication. The implications of current trends in molecular infectious diseases will provide a wealth of data regarding types of organisms present in a sample that will lead to more accurate and effective diagnosis and treatment of infectious diseases. In this issue, Alkhatib and Al-Balas (2021) state that health marketing has elevated the status of healthcare. Healthcare Marketing needs a planned medical marketing strategy to keep up your healthcare brand.